Do Smaller Firms Grow Faster than Large Enterprises? The Case of Czech Transportation and Storage Industry - Fiala, Roman; Hedija, Veronika (Communications - Scientific Letters of the University of Zilina, 2022)
The study is focused on the relationship between firm growth and firm size. The aim of this study is to examine the growth-size relationship and test Gibrat's law validity in the Czech transportation and storage industry. To examine the relationship between firm size and firm growth, the linear auto-regression model is applied. The sales and sum of total assets are used as indicators of the firm size. The final sample contains data for more than 6,000 Czech firms in the period 2008-2017. The results have shown that Gibrat's law is not valid in the Czech transportation and storage industry. Smaller firms tend to grow faster than larger ones. Due to the limited scope of data, we were only able to verify the validity of Gibrat's law. The data used do not allow to examine the factors influencing the faster growth of small companies compared to large companies. It will be the subject of further research.
Keywords: firm growth; firm size; Gibrat's law; transportation and storage industry